2000
DOI: 10.1038/sj.bmt.1702386
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt (TIPS) for severe veno-occlusive disease of the liver following bone marrow transplantation

Abstract: Summary:Severe veno-occlusive disease (VOD) of the liver is a leading cause of mortality after bone marrow transplantation (BMT). Vascular and parenchymal injuries account for acute portal hypertension and liver failure is frequently present. We describe the results of transjugular intrahepatic portosystemic shunt (TIPS) for the management of VOD after BMT. TIPS was performed in 10 patients with histologically proven severe VOD. Portal hypertension was controlled by TIPS in all patients (mean hepatic venous pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(33 citation statements)
references
References 24 publications
1
30
1
1
Order By: Relevance
“…Osler-Weber-Rendu sindromas 1 (1,9) Vilsono liga 1 (1,9) 3 lentelė. Ultragarso tyrimo duomenys matuojant TIPS veiksmingumą Remiantis nagrinėta literatūra buvo aktualu įvertinti, ar stento disfunkcija sukelia riziką atsirasti pakartotiniam kraujavimui ir refrakteriniam ascitui.…”
Section: Rezultataiunclassified
“…Osler-Weber-Rendu sindromas 1 (1,9) Vilsono liga 1 (1,9) 3 lentelė. Ultragarso tyrimo duomenys matuojant TIPS veiksmingumą Remiantis nagrinėta literatūra buvo aktualu įvertinti, ar stento disfunkcija sukelia riziką atsirasti pakartotiniam kraujavimui ir refrakteriniam ascitui.…”
Section: Rezultataiunclassified
“…Unfortunately, all but three died of other complications. There is some suggestion from the report of Azoulay and colleagues, 79 that responding patients have less severe disease, as demonstrated by lower bilirubin and ALT prior to the TIPS and a greater reduction in the hepatic venous pressure gradient after the procedure. In addition, their patients who died shortly after TIPS had a shorter interval from transplant to TIPS than patients who survived more than 10 days, suggesting that the pace of their disease was faster.…”
Section: Non-pharmacologic Therapy: Transjugular Intrahepatic Portosymentioning
confidence: 99%
“…A total of 19 patients have been reported in the literature. [76][77][78][79] Significant reduction in hepatic venous pressure gradient was reported after the procedure. Eight patients had no improvement in VOD and died within 2 weeks.…”
Section: Non-pharmacologic Therapy: Transjugular Intrahepatic Portosymentioning
confidence: 99%
“…59 It was reported that IL-1, TNFalpha, interferon gamma, IL-2 receptor-alpha and TNF-receptor levels increased in ES as in acute International Journal of Hematology and Oncology GVHD. 54 Soluble thrombomodulin and plasminogen activator type I, CRP increase and complement activation are changes detected in ES. 60 The incidence of ES is varying from 5% to 72% because the definition and criteria of ES are not described precisely.…”
Section: Engraftment Syndromementioning
confidence: 99%
“…33 Transjugular intrahepatic portosystemic shunt can be performed in patients who are unsuitable for surgery. 54 In advanced liver failure, liver transplantation can be a treatment option in few cases. …”
mentioning
confidence: 99%